Depigmented centella asiatica extraction by pretreated with supercritical carbon dioxide fluid for wound healing application - Warintorn Ruksiriwanich (2020)
© 2020 by the authors. Centella asiatica has been included in Thai traditional medicinal plants and recipes, as a well-established historical use as a vegetable and tonic. However, when applied in modern formulations, the progressive degradation of the plant pigments occurs, causing color-fading and color variation in the products. Depigmentation of the comminuted sample using supercritical carbon dioxide (scCO2) fluid extraction with a cosolvent was introduced as a pretreatment to solve the color-fading problem. The contents of compounds with known biological activities and the wound healing activities (antioxidant screening by DPPH and ABTS+ scavenging activities; cell migration assay; matrix metallopeptidase [MMP]-2 inhibition on human skin fibroblast; endothelial cell tube formation assay) of the C. asiatica leaf extracts obtained by conventional ethanolic extraction (CV) and pretreatment using scCO2 extraction, were determined. Total triterpenoids (madecassoside, asiaticoside B, asiaticoside, madecassic acid, terminolic acid and asiatic acid) and total triterpenoid glucosides (madecassoside, asiaticoside B and asiaticoside) were notably more abundant in the extract that had been pretreated using scCO2 than the extract obtained by CV. Moreover, the scCO2 pretreatment not only caused greater relative MMP-2 inhibition (58.48 ± 7.50% of the control), but also exhibited a higher cell migration (59.83 ± 1.85% of the initial) and number of vessels (18.25 ± 4.58) of angiogenesis in the wound healing process. Additionally, positive correlations were observed between the DPPH antioxidant activity and madecassoside content (r = 0.914, p < 0.01), as well as between the cell migration activity and asiaticoside content (r = 0.854, p < 0.05). It can be concluded that the scCO2 pretreatment of C. asiatica can eliminate color pigments from the extract and improve its in vitro wound healing activity.